2012
DOI: 10.19182/remvt.10132
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence des principales bactéries responsables de mammites subcliniques des vaches laitières au nord-est de l’Algérie

Abstract: Des analyses bactériologiques de 235 prélèvements de lait de vaches laitières atteintes de mammites subcliniques dépistées par le California mastitis test, provenant de dix exploitations du nord-est de l’Algérie, ont été réalisées  sur une période de deux ans (2008-10). L’isolement bactérien a concerné 89 p. 100 des échantillons. Parmi les germes isolés, les coques à Gram positif ont été les plus fréquents, notamment des staphylocoques à coagulase négative (43 p. 100) et Staphylococcus aureus (30 p. 100). Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…By comparison, sub-clinical mastitis was detected in 79% of cows examined in the northeast region of Algeria (Boufaida-Asnoune et al, 2012). While Aggad et al (2009) reported in western Algeria that mastitis was detected in 47% of individual milks, which is close to the results of our study.…”
Section: Resultssupporting
confidence: 91%
“…By comparison, sub-clinical mastitis was detected in 79% of cows examined in the northeast region of Algeria (Boufaida-Asnoune et al, 2012). While Aggad et al (2009) reported in western Algeria that mastitis was detected in 47% of individual milks, which is close to the results of our study.…”
Section: Resultssupporting
confidence: 91%
“…Mastitis is a common inflammation of the cow udder leading to defect in milk production quantitatively and qualitatively leading to economic losses. In the present study, 239 (66.4%) cows presented a positive CMT test which was in accordance with the previous study in Algeria where 79% of the tested cows were CMT + (Asnoune et al, 2012), and with the study on milk quality in West Algeria (Aggad et al, 2009). Escherichia coli can harbor and transmit resistance to antibiotics.…”
Section: Discussionsupporting
confidence: 93%
“…As well as the lowest recorded in Bangladesh 64.9% (Hoque et al, 2014), in Kenya 73.1% (Mbindyo et al, 2020) and in Uganda 86.2% (Abrahmsén et al, 2013). Furthermore, the incidence at quarter level was 31.1%, which was also higher than recorded in the northeast and central region of Algeria 23.6% (Boufaida et al, 2012) and 28.5% (Saidi et al, 2013), respectively, and in Senegal 11.9% (Kalandi et al, 2017). A plausible explication of this high prevalence in the study area could be that proper farming management and earlier screen for subclinical mastitis were not practiced.…”
Section: Discussionmentioning
confidence: 74%